1999
DOI: 10.2527/1999.7741016x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ruminal administration of supplemental degradable intake protein and starch on utilization of low-quality warm-season grass hay by beef steers.

Abstract: Hereford x Angus steers were used in a 13-treatment, four-period, incomplete Latin square design to examine the effects of starch and degradable intake protein (DIP) supplements on forage utilization and ruminal function. Steers were given ad libitum access to low-quality hay (4.9% CP) and were not supplemented (NS) or received different amounts of starch (cornstarch grits; 0, .15, and .3% of initial BW) and DIP (Na-caseinate; .03, .06, .09, and .12% of initial BW) administered via ruminal fistulae in a 3 x 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1
16

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 24 publications
8
46
1
16
Order By: Relevance
“…A redução no consumo de forragem em animais recebendo suplementos energéticos pode ser atribuída a mudanças nas proporções relativas das populações de microrganismos no rúmen em função da competição por substratos, principalmente N (Olson et al, 1999).…”
Section: -Means Coefficients Of Variation (Cv) and Probabilities (P)unclassified
“…A redução no consumo de forragem em animais recebendo suplementos energéticos pode ser atribuída a mudanças nas proporções relativas das populações de microrganismos no rúmen em função da competição por substratos, principalmente N (Olson et al, 1999).…”
Section: -Means Coefficients Of Variation (Cv) and Probabilities (P)unclassified
“…In this experiment, supplemental dextrose had no effect of forage intake. Olson et al (1999) reported that starch, at a level of 0.15% BW, decreased forage OMI in cattle, a bulk-grazer with much less capacity for selectivity than goats. It is not clear what the effect of dextrose would have been in the cattle of Olson et al (1999).…”
Section: Methodsmentioning
confidence: 99%
“…Olson et al (1999) reported that starch, at a level of 0.15% BW, decreased forage OMI in cattle, a bulk-grazer with much less capacity for selectivity than goats. It is not clear what the effect of dextrose would have been in the cattle of Olson et al (1999). The difference in the ruminal availability of starch and dextrose could be used to explain the differences in responses between dextrose and starch, since even different sources of starch result in differing goat forage intake (Abijaoudé et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Total faecal output was recorded for each individual before the morning and afternoon feeding. A sample of voided faeces was taken daily for each animal, mixed and pooled over the first five days of the eight-day collection period (Köster et al, 1996;Olson et al, 1999). Two separate sub-samples of faeces were taken and frozen at −10 ºC.…”
Section: Methodsmentioning
confidence: 99%
“…It is uncertain what caused the difference (P <0.05) in butyrate concentrations. According to Heldt et al (1999) and Olson et al (1999), supplemental energy is responsible for increased butyrate concentration in the rumen, and not the RDP source.…”
Section: Tablementioning
confidence: 99%